A simulation analysis of controlling rules for flexible pull systems. (5th January 2007) - Yu, Min-Chun; Greene, Timothy J.
The pull-type manufacturing system is known for its need for a frozen schedule, balanced workload and inability to handle fluctuations in demand. But today's research and development are addressing the ways to handle a pull-type system to accommodate greater fluctuations. One approach is to design the system with greater routing flexibility in that flexible machines and multiple part types are implemented. To enhance the efficiency of flexible systems, effective control mechanisms are required to direct parts and machines throughout the systems. The existing literature concerning control mechanism has primarily been devoted to push-type production systems. This simulation study examined the effects of machine selection rules and scheduling rules for a flexible multi-stage pull system. Results showed that machine selection rules have no significant difference on all performance measures, while several scheduling rules such as SLACK* and First Come First Served (FCFS) demonstrate better performance.